Recognisability of pictographs on electrical product surface amongst Malaysian consumers / Mohd Saipuddin Mohd Hasbullah - Mohd Hasbullah, Mohd Saipuddin (2015)
The increasing technical complexity of electrical products resulted in the creation of a substantial amount of pictographs to allow visual interactions between consumers and the products. Nevertheless, the emergence of these large amounts of different pictographs with the same intended meaning has led to a potentially confusing situation. This event has led to doubts on the effectiveness of pictographs on electrical equipments towards the consumers in Malaysia. This research is aimed to find out the ability to recognize pictographs depicted on electrical appliances and the factors contributing to it. Eighteen selected pictographs which represent six meanings (reference) were tested on four hundred and thirteen respondents purposively. Generally, the data obtained from an identifiability test justifies that most of the pictographs are poorly recognize. This test also ensures that the researcher was able suggest six pictographs to be chosen as a single pictograph to represent six references. The usage of a single pictograph is expected to increase the probability for it to be seen frequently which will then avoid confusion among the consumers. Furthermore, this research is attempt to investigate the relationship between personal factors of the consumers and the ability to recognize pictographs correctly, whereas the consumers’ response will be tested by using Chi-square test. The researcher uncovers that ‘gender’ and ‘occupation’ has a significant relationship towards the ability to recognize the pictographs correctly. This study also determines the respondents’ assessments towards the twin viewpoints of graphic integrity and conceptual meaningfulness. The researcher has established a guideline that suggests the follow up study should be done to determine how both of the layout factors can influence the effectiveness of the pictograph.